We are given the line equation:
\[
4x - y - 2 = 0.
\]
Since point \( P \) is equidistant from \( A(-5, 6) \) and \( B(3, 2) \), the condition \( PA = PB \) must hold. Therefore, we use the equation:
\[
PA^2 = PB^2.
\]
Step 1: Use the distance formula.
The distances from \( P(a, b) \) to \( A(-5, 6) \) and \( B(3, 2) \) are:
\[
\sqrt{(a + 5)^2 + (b - 6)^2} = \sqrt{(a - 3)^2 + (b - 2)^2}.
\]
Squaring both sides, we get:
\[
(a + 5)^2 + (b - 6)^2 = (a - 3)^2 + (b - 2)^2.
\]
Simplifying:
\[
a^2 + 10a + 25 + b^2 - 12b + 36 = a^2 - 6a + 9 + b^2 - 4b + 4.
\]
Combine like terms:
\[
16a - 8b + 48 = 0.
\]
Step 2: Solve the system of equations.
From the line equation \( 4x - y - 2 = 0 \), we can express \( b \) in terms of \( a \) as:
\[
b = 4a - 2.
\]
Substitute this into the simplified distance equation:
\[
16a - 8(4a - 2) + 48 = 0.
\]
Simplify:
\[
16a - 32a + 16 + 48 = 0,
\]
\[
-16a + 64 = 0.
\]
Solving for \( a \):
\[
a = 4.
\]
Substitute \( a = 4 \) into the equation for \( b \):
\[
b = 4(4) - 2 = 14.
\]
Final Answer:
The coordinates of point \( P \) are:
\[
\boxed{(4, 14)}.
\]